Effectiveness and Downstream Healthcare Utilization for Patients That Received Early Physical Therapy Versus Usual Care for Low Back Pain: A Randomized Clinical Trial. Issue 19 (1st October 2018) - Rhon, Daniel I.; Miller, Robert B.; Fritz, Julie M.
Abstract : Study Design: Randomized controlled trial. Objective: The aim of this study was to compare early physical therapy versus usual care in patients with low back pain. Summary of Background Data: Early physical therapy (PT) has been associated with reduced downstream healthcare utilization in retrospective studies, but not investigated prospectively in the military health system. Methods: Military service members seeking care from a general practitioner were recruited. Patients attended a 20-minute self-management class with focus on psychosocial resilience and then randomized to usual care only (UC) versus immediately starting a 3-week physical therapy program (PT). Primary outcome was the Oswestry Disability Index at 1 year. Secondary outcomes included Oswestry scores at 4- and 12-week follow-up, numeric pain rating scale, global rating of change, and healthcare utilization at 1 year. Analysis of covariance was used to compare differences between groups, significance set at 0.05. Trial Registration: clinicaltrials.gov: NCT01556581 Results: A total of 119 patients (mean age 27.2 years; mean BMI 27.8 kg/m 2 ; 15.1% female) enrolled (61 randomized to UC; 58 to PT). No between-group differences found on the Oswestry after 1 year. A between-group difference in Oswestry was present at 4 weeks (mean difference = 4.4; 95% CI: 0.41–10.1; P  = 0.042) favoring PT. Total 1-year mean healthcare costs did not differ significantly between groups (UC $5037; 95 CI $4171–$6082 and PT $5299; 95 CI $4367–$6431). The portion of total mean healthcare costs related to low back pain was lower for UC ($1096; 95% CI $855–$1405) compared to PT ($2016, 95% CI $1570–$2590). Conclusion: There was no difference between usual care and early PT after 1 year. PT provided greater improvement in disability after 4 weeks. As both groups improved, the impact of the education may have been underestimated. Patients in the PT group utilized greater back-pain-related healthcare resources, but overall healthcare costs did not differ compared to UC. Level of Evidence: 2